A Review on Islamic Micro-insurance Studies - Amelia Tri Puspita; Dwi Ratna Kartikawati (SMART Insight, 2022)
The global insurance system is growing rapidly in a large number of countries in the world, including Indonesia. OJK shows support for increasing the growth of the Islamic finance industry in Indonesia by establishing a Sharia micro-insurance product which was officially launched in 2014. Therefore, to maintain its existence it must be supported by good governance. So, this study aims to meet the development trend of Microinsurance research published by leading journals on microinsurance. The data analyzed consisted of 198 indexed research publications. The data is then processed and analyzed using the VoS viewer application to find out the bibliometric map of Islamic microinsurance research development.